Obstrução nasolacrimal congênita - Diagnóstico e tratamento - Schellini, Silvana Artioli [UNESP]; Cesar Gaiotto, P. [UNESP]; Campos Schellini, R. de [UNESP]; Silva, Maria Rosa Bet de Moraes [UNESP] (My University, 1994)
Patients with congenital nasolacrimal obstruction (CNLO) were evaluated at the Lacrimal Apparatus Service of Botucatu Faculty of Medicine - UNESP from 1990 to 1993. 45 children were seen at this period with CNLO. The diagnosis was confirmed by dacryocystography (DCG). Obstruction was unilateral in 77,7% of the patients; 68,1% at Arlt Sinus and 43,6% had lacrimal sac grade 1. Probing was made in children older than 6 months, under general anaesthesia, after DCG was performed. Cure was greater in children age 6 to 12 months with obstruction at Hasner's Valve and without dilation of lacrimal sac.
Congenital nasolacrimal obstruction - Diagnosis and treatment
Keywords: congenital nasolacrimal obstruction; dacryocystography; probing